The association of chronic pain and opioid withdrawal in men and women with opioid use disorder. (1st November 2022) - Ware, Orrin D.; Ellis, Jennifer D.; Dunn, Kelly E.; Hobelmann, J. Gregory; Finan, Patrick; Huhn, Andrew S.
Abstract: Background: Approximately 2.7 million individuals in the United States had an opioid use disorder (OUD) in 2020. Chronic pain may exacerbate opioid withdrawal severity, yet most research on opioid withdrawal has not collected data on chronic pain status. Moreover, there is limited evidence that women tend to experience greater opioid withdrawal severity than men, but large, confirmatory studies on this topic have not been published. The goal of this study was to examine the roles of chronic pain and gender on opioid withdrawal severity using a large, multi-site database. Methods: Data were collected from N = 1252 individuals with OUD entering eight residential addiction treatment facilities. Demographic, drug use behaviors, and chronic pain status were collected at treatment intake, and self-reported opioid withdrawal and craving were measured at intake and 1–3 days, 4–6 days, and 7–9 days after intake. Regression analyses were used to predict withdrawal and craving severity at intake and across the four timepoints. Results: At intake, withdrawal was higher in persons who were older, had greater SUD severity, women, had chronic pain, and used > 1 substance (p-values ≤.007) and craving was higher in persons with greater SUD severity (p < .001) and women (p = .033). Withdrawal remained higher in women and persons with chronic pain across timepoints but decreased at a similar rate relative to comparators. Conclusions: Women and persons with chronic pain would benefit from earlier engagement in treatment and may require a more intensive strategy to mitigate opioid withdrawal in early treatment. Highlights: Compared to men, women entered treatment with greater withdrawal severity. Persons with chronic pain experienced greater withdrawal severity across timepoints. Women with chronic pain evidenced the greatest withdrawal severity among subgroups. Increased withdrawal severity was associated with strong/overpowering craving.